Genetic variations in innate immunity genes affect response to Coxiella burnetii and are associated with susceptibility to chronic Q fever. (May 2019) - Jansen, A.F.M.; Schoffelen, T.; Bleeker-Rovers, C.P.; Wever, P.C.; Jaeger, M.; Oosting, M.; Adriaans, A.; Joosten, L.A.B.; Netea, M.G.; van Deuren, M.; van de Vosse, E.
Abstract: Objectives: Chronic Q fever is a persistent infection, mostly of aortic aneurysms, vascular prostheses or damaged heart valves, caused by the intracellular bacterium Coxiella burnetii . Only a fraction of C . burnetii- infected individuals at risk develop chronic Q fever. In these individuals, a defective innate immune response may contribute to the development of chronic Q fever. We assessed whether genetic variations in genes involved in the killing machinery for C . burnetii by macrophages, contribute to the progression to chronic Q fever. Methods: The prevalence of 66 single nucleotide polymorphisms (SNPs) in 31 genes pivotal in phagolysosomal maturation, bacterial killing and autophagy, was determined in 173 chronic Q fever patients and 184 controls with risk factors for chronic Q fever and serological evidence of a C . burnetii infection. Associations were detected with univariate logistic regression models. To assess the effect of these SNPs on innate responses to C . burnetii, the C . burnetii -induced cytokine production and basal reactive oxygen species production of healthy volunteers was determined. Results: RAB7A (rs13081864) and P2RX7 loss-of-function SNP (rs3751143) were more common in chronic Q fever patients than in controls. RAB5A (rs8682), P2RX7 gain-of-function SNP (rs1718119), MAP1LC3A (rs1040747) and ATG5 (rs2245214) were more common in controls. In healthy volunteers, RAB7A (rs13081864) and MAP1LC3A (rs1040747) influenced the C . burnetii -induced cytokine production. RAB7A (rs13081864) modulated basal reactive oxygen species production. Conclusions: RAB7A (rs13081864) and P2RX7 (rs3751143) are associated with the development of chronic Q fever, whereas RAB5A (rs8682), P2RX7 (rs1718119), MAP1LC3A (rs1040747) and ATG5 (rs2245214) may have protective effects.